Migration and Higher Education in Poland (Economic and Political Thought, 2024)
The article presents reflections on migration and its role in the area of higher education in Poland. It highlights the problems and difficulties faced by foreign students studying in Poland.
Keywords: migration, higher education, Polish Law on Higher Education and Science